ANALYSIS OF THE ABILITY TO PAY CONTRIBUTIONS FOR PARTICIPANTS IN THE NATIONAL HEALTH INSURANCE (JKN) FOR NON-WAGE RECIPIENT WORKERS (PBPU) IN KOTA BARU AND JAMBI SELATAN SUBDISTRICTS IN 2021 - Royyan, Nurmisbahur; Noerjoedianto, Dwi; Solida, Adila; Ena Sari, Rumita; Nurwaqiah Ibnu, Ismi (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. The ability to pay or ability to pay (ATP) is defined as a person's ability to pay for a service or service he receives based on income that is considered ideal. A total of 586,893 (94.55%) residents of Jambi City have become participants in the National Health Insurance (JKN), but the high number of JKN participants is not accompanied by the active participation of the participants in paying monthly fees. as many as 77,489 participants in class I-III. The purpose of this study was to determine the analysis of the ability to pay the contributions of PBPU national health insurance (JKN) participants. Methods. Quantitative study with cross sectional design sample were 83 participants of the national health insurance (JKN) PBPU. Sample taken with cluster sampling technique. Results & Analysis. The variable ownership of assets has a correlation with the ability to pay contributions with (p = 0.020) and PR (5.379) and the income variable has no correlation with the ability to pay contributions with (p = 0.191) and PR (2.356). There was correlation between asset ownership and the ability to pay contributions for PBPU national health insurance (JKN) participants in Kota Baru and Jambi Selatan sub-districts. Discussion. It is hoped that there will be coordination between BPJS and the Social Service departement regarding the participants who have been registered for contribution assistance recipients (PBI) and re-examine whether the participants really fall into the category of the poor and cannot afford, so that they are entitled to receive contribution assistance.